Penerapan Model Talking Stick Berbantuan Media Gambar pada Pembelajaran PPKN - Pikri, Nurul; Supriyanto, Supriyanto; Charli, Leo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine the completeness of learning outcomes for PPKN subjects in class V of SDN 1 Terawas after treatment by implementing the Talking Stick Model Assisted by Image Media. The research method used is a quantitative approach with a pre-experimental research design of one group pretest-posttest. The research showed that the average post-test result was 85.2 with a completion percentage of 86.7% (13 students), while for students who did not complete it was 13.3% (2 students). The results of the data analysis show that Zcount ≥ Ztable is 3.30 ≥ 1.64. The conclusion is that the PPKN learning outcomes of class V students of SDN 1 Terawas after implementing the Talking Stick learning model assisted by picture media are significantly significant. Keywords: Learning Outcomes, Image Media, PPKN, Talking Stick